Relación entre la educación y las preferencias de fecundidad en México: lecciones de Italia - Juárez, Fatima; De Rose, Alessandra; Testa , Maria Rita (El Colegio de México A.C., 2024)
Education is an important determinant of reproductive preferences. However, few studies have explored the evolution of its role in countries with different levels of fertility transition, due to the lack of adequate data. In this paper, we analyze the role of education as a determinant of fertility preferences in Mexico, a country which is rapidly approaching the end of fertility transition, albeit with substantial differences between different areas of the country. Using survey data, we contrast the results with evidence from a very low fertility country, Italy. The results indicate a persistent negative correlation between fertility preferences and educational levels in Mexico. However, a more detailed analysis at the territorial level reveals that in the most developed regions—such as Mexico City—the relationship is going into reverse, with more educated women showing a greater willingness to having another child, similarly to Italy, where higher levels of education have a positive effect on fertility intentions.